(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Education is the process of the facilitation, learning or the gaining of knowledge, skill values beliefs and habits. Education plays a vital role in the shaping individual, societies, and nations. So, Adult education is important those who dropout the education in different levels. Different motivational factors motive them to rejoin the school in different levels. This research explores the challenges faced by the adult students in re-entering formal education and to analyze the key motivational factors motivating adult students to pursue further education. This study is based on qualitative method. In-depth interview was conducted with 8 participants who are studying in different grades. Interpretative research paradigm and exploratory research design are used to collect the information. This study highlights the intrinsic motivational factors like Desire for personal growth and development, Self-fulfillment and achievement, Family encouragement, and Self-Efficacy and Confidence to enroll in the school in various levels.